Expression analysis of HLA-E and NKG2A and NKG2C receptors points at a role for natural killer function in ankylosing spondylitis. Issue 2 (13th July 2018) - Cauli, Alberto; Dessole, Grazia; Piga, Matteo; Angioni, Maria Maddalena; Pinna, Silvia; Floris, Alberto; Congia, Mattia; Mascia, Enrico; Paladini, Fabiana; Tedeschi, Valentina; Sorrentino, Rosa; Fiorillo, Maria Teresa; et al.
Abstract : Background: Ankylosing spondylitis (AS) is a complex chronic inflammatory disease strongly associated with the majority of human leucocyte antigen (HLA)-B27 alleles. HLA-E molecules are non-classical major histocompatibility complex (MHC) class I molecules that specifically interact with the natural killer receptors NKG2A (inhibitory) and NKG2C (activating), and have been recently proposed to be involved in AS pathogenesis.'' Objective: To analyse the expression of HLA-E and the CD94/NKG2 pair of receptors in HLA-B27-positive patients with AS and healthy controls (HC) bearing the AS-associated B*2705 and the non-AS-associated B*2709 alleles. Methods: The level of surface expression of HLA-E molecules on CD14+ peripheral blood mononuclear cell was evaluated in 21 HLA-B*2705 patients with AS, 12 HLA-B*2705 HC, 12 HLA-B*2709 HC and 6 HLA-B27-negative HC using the monoclonal antibody MEM-E/08 by quantitative cytofluorimetric analysis. The percentage and density of expression of HLA-E ligands NKG2A and NKG2C were also measured on CD3−CD56+ NK cells. Results: HLA-E expression in CD14+ cells was significantly higher in patients with AS (587.0, IQR 424–830) compared with B*2705 HC (389, IQR 251.3–440.5; p=0.0007), B*2709 HC (294.5, IQR 209.5–422; p=0.0004) and HLA-B27-negative HC (380, IQR 197.3–515.0; p=0.01). A higher number of NK cells expressing NKG2A compared with NKG2C were found in all cohorts analysed, as well as a higher cell surface density. Conclusion: The higher surface level of HLA-E molecules in patients with AS compared with HC, concurrently with a prevalent expression of NKG2A, suggests that the crosstalk between these two molecules might play a role in AS pathogenesis, accounting for the previously reported association between HLA-E and AS.